Lighting Intensity Analysis in The Biology Practicum Room at The Integrated Laboratory of UIN Sunan Ampel Surabaya - Rokhim, Saiku (International Conference on Sustainable Health Promotion, 2018)
Lighting is one of the essential factors to support human work productivity. Therefore the use of lighting intensity has to be adjusted to the activities in a room. One room with a particular lighting intensity is a practicum room. The purpose of this study is to analyze the intensity of lighting especially in the Biology practicum room at the Integrated Laboratory of UIN Sunan Ampel Surabaya. The method of the research uses quantitative approach. The data are derived from the measurement and observation of the research object. The study was conducted on six Biology's practicum rooms located on the 3rd floor of Integrated Laboratory Building of UIN Sunan Ampel Surabaya which included practicum room for Biochemistry, Genetics, Ecology, Basic Biology A, Microbiology, and Basic Biology B. Primary data was obtained by measuring lighting in space using lux meter. The measured lighting focus is general lighting. The measurement data were then collected and analyzed by comparing them to SNI 03-6197-2000. The results show that all Biology's practicum rooms have windows that function as natural lighting from sunlight and are supported by artificial lighting sourced from lamps. In the measurements of six Biology's practicum rooms, there is a mismatch of lighting intensity to SNI 03-6197-2000 which includes a practicum of Ecology, Basic Biology A, and Microbiology. But the discrepancy is only at certain points. The suggestion is the need to replace the extinguished lamps at some measurement points so it can increase the intensity of the lighting in the room.